Active surveillance as a therapeutic option for patients with low-risk prostate cancer according to the 2014 International Society of Urological Pathology grading system: a review. (2nd January 2017) - Helpap, Burkhard; Gevensleben, Heidrun
Abstract: Extended prostate-specific antigen screening and the tightly focused execution of biopsies have resulted in an increased rate of detection, and thereby increased interventional treatment, of prostate cancer (PCa). The potential overdiagnosis and overtreatment of PCa patients have repeatedly been criticized in national and international literature. Controlled monitoring of patients in the setting of active surveillance (AS) can prevent overtreatment and the needless impairment of quality of life. The prerequisite for this treatment strategy is the diagnosis of low-grade/risk PCa. Since 2005, the modified Gleason grading system has been used for the histological assessment of PCa. In 2014, the International Society of Urological Pathology recommended a new prognostic grading system with five grades analogous to the modified Gleason score. This review discusses the importance of pathological histological analysis of PCa, particularly in the face of recent amendments, and sheds light on the significance of the new grading system for the diagnosis of low-grade/risk PCa with regard to the therapeutic option of AS.